The Protozoa and helminths in the water of Terme and Kocaman Boroughs of Samsun Province (Annals of Medical Research, 2021)
Aim: It was aimed to determine the presence of parasites and helminths in the environmental waters of the Terme and Kocaman districts of Samsun.Meterial and Methods: In this study, 6 stations in Terme and 6 stations in Kocaman Miliç River areas were included.The research was conducted between August 2012 - July 2013 and every month water samples were collected. The pellet part of the supernatant samples was examined on the same day by native-lugol methods. The samples were also examined by kinyoun acid fast, Weber’s modified trichrome and trichrome methods. The samples were painted and evaluated according to parasitologic terms.Results: As a result of water sample examination, 144 Cryptosporidium spp., oocysts 96 Cyclospora spp., oocysts 60 Strongyloides spp., larvae 36 Microsporidia spores, 48 Blastocystis spp. granular forms, 24 Chilomastix spp. trophozoits, 24 Balantidium spp. trophozoits, 60 hookworm eggs and 132 Giardia spp. cysts have been observed.Conclusion: The animal husbandry made in those regions, direct discharge of the waste water pipes into the river, the usage of this water for irrigation and animal drinking and water cooling explain the presence of parasites in the water. As water is an agricultural, industrial and domestic requirement, it should be free of pathogenic microorganisms in accordance with the criteria related to its potential use. Water, which is a domestic requirement for agriculture and industry, needs to be purified from pathogenic microorganisms in accordance with the criteria for its potential use.Keywords: Terme; Kocaman; Environmental Waters; Parasites.